Scoping the needs, roles and implementation of bilingual community navigators in general practice settings. (25th August 2022) - Mistry, Sabuj Kanti; Harris, Elizabeth; Harris, Mark F.
Abstract: This research aimed to explore the needs, potential roles and implementation of Bilingual Community Navigators (BCNs) in providing navigation support for patients in general practice settings in Australia. A total of 19 participants (general practitioners, practice managers, practice nurses and receptionists) from five general practices in Sydney where most of the patients spoke a language other than English were interviewed about their views on needs, potential roles and implementation of BCNs in general practice settings. Data were collected between August 2019 and July 2020. The interview transcripts were inductively analysed for themes. Themes emerged across four broad categories: patients' barriers to access health and social care services; potential roles of BCNs; recruitment, training, and employment of BCNs and considerations and anticipated barriers to BCNs' role. Many barriers both at the patient and at the service provider levels in accessing healthcare and social care services were consistent with the Levesque et al. access framework including lack of understanding of the health system, language and cultural barriers, hesitancy to approach general practice and problems navigating services. Participants believed that BCNs would be able to help overcome these barriers through health education, support in booking appointments, arranging transport, providing language and cultural support and improving communication with the health services. Conditions for effective implementation of BCNs in practice included proper training of the navigators to ensure patient confidentiality and addressing organisational/system barriers such as lack of a funding mechanism, a clear role definition of BCNs and acceptance of BCNs by patients. BCNs potential role in facilitating access to appropriate care by culturally and linguistically diverse (CALD) patients in general practice warrants further evaluation in the context of the Australian healthcare system.